Bioadhesive eutectogels supporting drug nanocrystals for long-acting delivery to mucosal tissues. (15th December 2022) - Bianchi, María Beatrice; Zhang, Chunyang; Catlin, Elise; Sandri, Giuseppina; Calderón, Marcelo; Larrañeta, Eneko; Donnelly, Ryan F.; Picchio, Matías L.; Paredes, Alejandro J.
Abstract: Eutectogels (Egels) are an emerging class of soft ionic materials outperforming traditional temperature-intolerant hydrogels and costly ionogels. Due to their excellent elasticity, non-volatile nature, and adhesion properties, Egels are attracting a great deal of interest in the biomedical space. Herein, we report the first example of adhesive Egels loading drug nanocrystals (Egel-NCs) for controlled delivery to mucosal tissues. These soft materials were prepared using gelatin, glycerine, a deep eutectic solvent (DES) based on choline hydrochloride and glycerol, and nanocrystallised curcumin, a model drug with potent antimicrobial and anti-inflammatory activities. We first explored the impact of the biopolymer concentration on the viscoelastic and mechanical properties of the networks. Thanks to the dynamic interactions between gelatin and the DES, the Egel showed excellent stretchability and elasticity (up to ≈160%), reversible gel-sol phase transition at mild temperature (≈50 ​°C), 3D-printing ability, and good adhesion to mucin protein (stickiness ≈40 ​kPa). In vitro release profiles demonstrated the ability of the NCs-based Egel to deliver curcumin for up to four weeks and deposit significantly higher drug amounts in excised porcine mucosa compared to the control cohort. All in all, this study opens new prospects in designing soft adhesive materials for long-acting drug delivery and paves the way to explore novel eutectic systems with multiple therapeutic applications. Graphical abstract: Image 1